Prioritization of production strategies of a manufacturing plant by using an integrated intuitionistic fuzzy AHP & TOPSIS approach. Issue 4 (9th July 2018) - Karasan, Ali; Erdogan, Melike; Ilbahar, Esra
Abstract : Purpose: The purpose of this paper is to find most appropriate production strategy for a manufacturing plant by using an integrated interval-valued intuitionistic fuzzy (IVIF) analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) approach. Design/methodology/approach: The applied methodology is a multi-criteria decision making approach consists of AHP and TOPSIS methods with the extension of intuitionistic fuzzy sets. Findings: Results of the application are revealed that using integrated IVIF-AHP & TOPSIS methods are very appropriate for the prioritization of the strategy for the production management for a manufacturing plant. This outcome also is supported by the sensitivity analysis. Results of the sensitivity analysis demonstrate the robustness of the methodology. Originality/value: To the best of the authors' knowledge, an integrated IVIF-AHP & TOPSIS methodology is used for the prioritization of production strategies for the first time.